Metal ion and pH Stable Protease Production Using Agro-industrial Waste - Rajni Singh2*, Rajshree Saxena1 and (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Protease from a newly isolated Bacillus strain exhibited stability in presence of many monovalent and divalent ions and a wide pH range. Agro-industrial waste as Wheat Bran, Gram Husk, Rice Bran and Mustard Oil Cake were used for the production of the enzyme in Solid state fermentation. Maximum enzyme production was observed with rice bran at moisture content 1:3 (w/v) and 20% inoculum size (v/w). The optimum temperature and pH of the enzyme activity were found to be 60oC and 8 respectively. It was found to be stable at 30-50<span style="font-size: 10pt; line-height: 110%; font-family: Symbol; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-ascii-font-family: Garamond; mso-hansi-font-family: Garamond; mso-char-type: symbol; mso-symbol-font-family: Symbol;">°<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">C for 2 h and pH range of 6-9. The enzyme activity enhanced in presence of metal ions as Na+, K+, Ca++, Mg++ Cu++, Mn++, Zn++ and Hg++ the activity. --------------------------------------------------------------------- 1Amity Institute of Biotechnology, Amity University, Noida, Uttar Pradesh, India 2Amity Institute of Microbial Biotechnology, Amity University, Noida, Uttar Pradesh, India *Corresponding author, Email: rsingh3@amity.edu, Tel: 0120-4392900, Fax: 0120-4392295 Please Cite This Article As: <span style="font-size: 8.5pt; font-family: Symbol; mso-ascii-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-char-type: symbol; mso-symbol-font-family: Symbol; mso-bidi-font-size: 10.0pt;"> <span style="font-size: 10.5pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Rajshree Saxena and Rajni Singh. 2010. Metal ion and pH Stable Protease Production Using Agro-industrial Waste. J. Ecobiotechnol. 2(4):01-05.